2020
DOI: 10.3389/fmicb.2020.02101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Insights Into the Molecular Basis of SARS-CoV-2 Infection: What We Can Learn From the Human Olfactory Axis

Abstract: Like other RNA viruses, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replicates in host cells, continuously modulating the molecular environment. It encodes 28 multifunctional proteins that induce an imbalance in the metabolic and proteostatic homeostasis in infected cells. Recently, proteomic approaches have allowed the evaluation of the impact of SARS-CoV-2 infection in human cells. Here, we discuss the current use of proteomics in three major application areas: (i) virus-protein interactomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Due to our experimental design, the overexpression of exogenous proteins may generate drawbacks concerning protein misfolding, localization and regulation as well as intrinsic limitations associated to GFP expression systems (Jensen, 2012). Based on the olfactory cellular system used, additional experiments are needed to verify the specific role of the SARS-CoV-2 structural proteome in different human olfactory cellular contexts (Lachen-Montes et al, 2020;Hatton et al, 2021). As shown in previous reports performed at cellular and tissular levels (Nie et al, 2021;Stukalov et al, 2021), the application of proteomics in different olfactory cell layers as well as in olfactory areas directly derived from COVID-19 individuals, would increase our understanding of not only the early smell impairment associated to SARS-CoV-2 infection but also the olfactory recovery potential in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to our experimental design, the overexpression of exogenous proteins may generate drawbacks concerning protein misfolding, localization and regulation as well as intrinsic limitations associated to GFP expression systems (Jensen, 2012). Based on the olfactory cellular system used, additional experiments are needed to verify the specific role of the SARS-CoV-2 structural proteome in different human olfactory cellular contexts (Lachen-Montes et al, 2020;Hatton et al, 2021). As shown in previous reports performed at cellular and tissular levels (Nie et al, 2021;Stukalov et al, 2021), the application of proteomics in different olfactory cell layers as well as in olfactory areas directly derived from COVID-19 individuals, would increase our understanding of not only the early smell impairment associated to SARS-CoV-2 infection but also the olfactory recovery potential in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Omics technologies have allowed to increase our knowledge about the molecular imbalance triggered by the SARS-CoV-2 in multiple human organs as well as in-vitro systems (Lachen-Montes et al, 2020;Nie et al, 2021;Saccon et al, 2021;Stukalov et al, 2021). However, there are still major gaps in the pathways leading to loss of smell caused by SARS-CoV-2, in addition to the molecular consequences from SARS-CoV-2 structural proteins at the olfactory level.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of MS-based proteomics, over 5000 new plasma protein biomarkers have been discovered [23]. In the context of COVID-19, proteomic studies revealed COVID-19 pathology [24][25][26][27][28] and associated characteristics of plasma protein [29], serum [30], and prognostic markers [31]. MS-based lipidomics has shed significant insights into biomarkers, inflammation, infection, and biological profiles associated with COVID-19 [32][33][34][35][36][37][38], gut microbiome alterations [39], and drug response [40].…”
Section: Mass Spectrometry In Disease Researchmentioning
confidence: 99%
“…Sixteen Nsps (Nsp1–Nsp16) of SARS-CoV-2 play a crucial role in viral replication and escape from the host immune response. LC-MS/MS has been used to study the protein-protein interactions (PPIs) between the host and virus to elucidate the host immune response and potential drug targets [ 21 ]. Hence, targeting these proteins may lead to better therapeutic approaches against COVID-19 [ 22 ].…”
Section: Proteomics-based Approaches For Understanding Covid-19 and Drug Discoverymentioning
confidence: 99%